Persuasive Linguistic Strategies in Indonesian E-Commerce Campaigns for the 2021 Pandemic Marketing Framework - Maharani, Putri; Paendong, Stevean Misael; Amiruddin, Nurhalimah (Lingua Cultura, 2024)
The research examined the use of persuasive linguistic strategies in the marketing campaigns of Indonesia’s top e-commerce platforms during the COVID-19 pandemic in 2021. The research analyzed media coverage data collected manually over the year, focusing on Tokopedia, Shopee, Bukalapak, Lazada, and Blibli. Each platform utilized unique linguistic techniques to address consumer concerns and maintain trust amidst the crisis. Emotive appeals, such as language evoking safety and community, urgency through time-sensitive offers, and social proof showcasing widespread acceptance, were used to influence consumer behavior. The analysis reveals that Blibli emphasizes strategic partnerships and acquisitions, while Shopee employs aggressive promotional campaigns. Tokopedia highlights national pride and community support, Bukalapak focuses on government collaborations, and Lazada has limited promotional impact compared to its competitors. The research demonstrates that Lazada’s slower growth is tied to its underutilization of persuasive language, highlighting the importance of linguistic strategies in maintaining consumer trust and market visibility during crises. The research contributes to understanding how persuasive language can serve as a critical marketing strategy in times of uncertainty, with platforms like Shopee and Tokopedia successfully leveraging these techniques to engage consumers. Limitations include potential data incompleteness due to manual tracking methods, and future research is recommended to explore consumer responses to these advertising strategies.